2019
DOI: 10.1021/acs.biochem.9b00290
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomics Using Nucleotide Acyl Phosphates Reveals an ATP Binding Site at the Dimer Interface of Procaspase-6

Abstract: Acyl phosphates of ATP (ATPAc) and related nucleotides have proven to be useful for the interrogation of known nucleotide binding sites via specific acylation of conserved lysines (K). In addition, occasional K acylations are identified in proteins without such known sites. Here we present a robust and specific acylation of procaspase-6 by ATPAc at K133 in Jurkat cell lysates. The K133 acylation is dependent on π–π stacking interactions between the adenine moiety of ATPAc and a conserved Y198–Y198 site formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Closer in function to caspases, granzyme A and granzyme B, which can also induce cell death in a caspase-dependent (granzyme B) or independent (granzyme A) manner, bind RNA and DNA with nanomolar affinity and cleave RNA-BPs faster in the presence of nucleic acids (30). Our findings expand the body of evidence for the existence of regulatory sites on caspases, including by metallic ions (31) and small molecules like the nucleotide ATP (32). With our findings, these findings also increase the potential for design of caspase modulators targeting regions other than the canonical catalytic site and maybe achieve better selectivity.…”
Section: Discussionsupporting
confidence: 74%
“…Closer in function to caspases, granzyme A and granzyme B, which can also induce cell death in a caspase-dependent (granzyme B) or independent (granzyme A) manner, bind RNA and DNA with nanomolar affinity and cleave RNA-BPs faster in the presence of nucleic acids (30). Our findings expand the body of evidence for the existence of regulatory sites on caspases, including by metallic ions (31) and small molecules like the nucleotide ATP (32). With our findings, these findings also increase the potential for design of caspase modulators targeting regions other than the canonical catalytic site and maybe achieve better selectivity.…”
Section: Discussionsupporting
confidence: 74%
“…However, after 24 h aging, the measurement declines to 0.15 mM and 0.13 mM, respectively. The results are consistent with previous studies, 17,30 which indicated that, without the interference of other substances in the cells, the developed method can be used for monitoring ATP concentrations in cell extracts.…”
Section: Resultssupporting
confidence: 92%
“…ATP can be generated from photosynthesis, cellular respiration, and multifunctional nucleoside. In many cellular movement and activities of metabolism and signaling, a plenty of enzymes consume ATP when the energy is moved throughout the cells in the biological processes, like muscle contractions, ions and molecules movement, biosynthesis of significant molecules, digestion and absorption of food, [14][15][16][17] etc. Additionally, during the synthesis process of DNA replication and transcription, ATP can be incorporated into nucleic acid through polymerases.…”
Section: Introductionmentioning
confidence: 99%
“…31 Caspase-6 constructs were purified as previously described via the procaspase-6 (caspse-6 C163S) purification protocol. 32 Caspase-9 was purified as previously described via the caspase-9 full-length purification protocol. 31 The purity and concentrations of purified caspases were assessed by sodium dodecyl sulfate− polyacrylamide gel electrophoresis (SDS−PAGE), and aliquots were stored at −80 °C until further usage for different assays.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%